2014
DOI: 10.5195/ijms.2014.83
|View full text |Cite
|
Sign up to set email alerts
|

Sub-tenon Anaesthesia versus Intracameral Anaesthesia in Patients Undergoing Cataract Extraction: A Comparative Study of the Level of Pain, Visual Perception and Anxiety

Abstract: Background: Phacoemulsification is a modern method of cataract extraction. Sub-tenon anaesthesia used to be the preferred anaesthetic technique for this procedure before intracameral anaesthesia gained its popularity in recent years. Nevertheless, many surgeons still believe that sub-tenon anaesthesia is better than topical anaesthesia. This study aimed to evaluate and compare the experiences of patients who were treated for cataract by phacoemulsification surgery using either sub-tenon or intracameral anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Numerous studies have been done worldwide showing favourable results for topical anaesthesia in cataract surgery. In Malaysia, a comparative study was performed for the level of pain, visual perception and anxiety in 62 patients given either subtenon or intracameral anaesthesia [3]. They found no significant differences in the level of pain experiences between the 2 groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been done worldwide showing favourable results for topical anaesthesia in cataract surgery. In Malaysia, a comparative study was performed for the level of pain, visual perception and anxiety in 62 patients given either subtenon or intracameral anaesthesia [3]. They found no significant differences in the level of pain experiences between the 2 groups of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies reported no significant differences in pain control between intracameral anesthesia and topical anesthesia. Mustapha et al 19 reported that intracameral anesthesia obviates the need for an injection during cataract surgery and is as comfortable for patients as sub-Tenon anesthesia in terms of visual perception, level of pain, and anxiety.…”
Section: Introductionmentioning
confidence: 99%